A cena musical indie em Belo Horizonte: novos padrões de carreira no interior de uma cena local - Rafael Sanzio Nunes Fonseca (2011)
This essay presents the results of a sociological research that concerns what may be called the indie music scene of Belo Horizonte. More specifically, it seeks to ascertain the career patterns within such a scene. While the concept of career, as understood in its relationship with the so-called Chicago School, tries to cope with the subjective choices of agents (bands) before the objective possibilities they face in their daily activity, the term scene aspires to join the present-day's perspective, which develops according to a diversity of disciplinary domains. One aim is to point to the inadequacy of a theoretical construct that intends to delimit the population under study according to stylistic definitions or formal/entrepreneurial ones. At the same time it refers to the reality of the band's activities, in the form of a network constituted by them in the occasions that they succeed each other onstage as a way of bounding the intended sociological synthesis' referral